Investigating endocannabinoid system and subjective responses to exercise in cancer patients: Rationale and future research directionsKey Points - Abha Gourshettiwar; Judith Lacey; Shelley Kay; Justine Stehn; Mitchell Low; Birinder S. Cheema (Elsevier, 2024)
Over forty years of evidence supports the integration of exercise therapy in cancer care. However, most cancer patients remain insufficiently active due in part to subjectively reported treatment-related side effects (and late effects) including fatigue, pain, appetite dysregulation, insomnia, cognitive impairment, depression, anxiety, low self-efficacy, and poor motivation. Many of these symptoms can be mitigated with exercise. However, the biological mechanisms by which exercise attenuates these cancer treatment-related side effects remain to be elucidated. This article presents a rationale for the investigation of endocannabinoid system (ECS) responses to exercise in cancer patients. We provide an overview of the ECS and preliminary evidence of ECS dysfunction induced by cancer, its risk factors (comorbidities) and cancer treatment. Further, we present a brief review of evidence from non-cancer cohorts demonstrating that acute (single bout) and chronic (>12 week) exercise can induce changes in circulating endocannabinoids (e.g. N-arachidonoylethanolamine (AEA or anandamide), 2-arachidonoylglycerol (2-AG) and related biogenic lipids). These changes are consistently accompanied by improvements in many subjectively reported, affective (mood) states (i.e. psychological outcomes) including sense of well-being, euphoria, vigour, anxiety, depression, fatigue, confusion, tension, mood disturbance, and pain. Given the substantial overlap between these subjective outcomes and the adverse effects that commonly arise as a consequence of cancer treatment, we clarify avenues for future research directed at improving our understanding of how cancer treatments negatively affect the ECS and patient symptomology, and how exercise may biologically mitigate these sequelae.